Severely Heat Injured Survivors of E. coli O157:H7 ATCC 43888 Display Variable and Heterogeneous Stress Resistance Behavior - Gayán, Elisa; Govers, Sander K.; Michiels, Chris W.; Aertsen, Abram (Frontiers in Microbiology, 2016)
Although minimal food processing strategies aim to eliminate foodborne pathogens and spoilage microorganisms through a combination of mild preservation techniques, little is actually known on the resistance behavior of the small fraction of microorganisms surviving an inimical treatment. In this study, the conduct of severely heat stressed survivors of E. coli O157:H7 ATCC 43888, as an indicator for the low infectious dose foodborne enterohaemorrhagic strains, was examined throughout their resuscitation and outgrowth. Despite the fact that these survivors were initially sublethally injured, they were only marginally more sensitive to a subsequent heat treatment and actually much more resistant to a subsequent high hydrostatic pressure (HHP) shock in comparison with unstressed control cells. Throughout further resuscitation, however, their initial HHP resistance rapidly faded out, while their heat resistance increased and surpassed the initial heat resistance of unstressed control cells. Results also indicated that the population eventually emerging from the severely heat stressed survivors heterogeneously consisted of both growing and non-growing persister-like cells. Together, these observations provide deeper insights into the particular behavior and heterogeneity of stressed foodborne pathogens in the context of food preservation.